Novel HPLC analysis of cefadroxil in bulk formulation - Shukla, Ravi Shankar; Pandey, S; Bargale, Rajesh (Asian Journal of Pharmaceutics (AJP), 2014)
A rapid, accurate, and sensitive method has been developed and validated for the quantitative determination of cefadroxil (first generation) in bulk form. An Inertsil ODS, 4.60 Ã— 250 mm2, 5 Î¼m analytical column was used with an eluting system consisting of a mixture of phosphate buffer (pH 6.5)-methanol 78-32% (v/v) at a flow-rate 1.5 ml/min. Detection was performed by UV-Vis detector at 210 nm, resulting in limit of detection of 0.06 ppm for cefadroxil per 20-Î¼l injection. A linear relationship was observed up to 0.2 ppm for cefadroxil. Analysis time was less than 10 min. The statistical evaluation of the method was examined by means of within-day repeatability (n = 6) and day-to-day precision (n = 7) and was found to be satisfactory with high accuracy and precision. The method may be applied for the determination of the cefadroxil in bulk formulation in future. Key words: Cefadroxil, cephalosporins, HPLC, phosphate buffer